2015
DOI: 10.1002/celc.201500396
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Platinum in the Operational Range of Fuel Cells

Abstract: The front cover artwork is provided by the Electrocatalysis Group at the Max‐Planck‐Institut für Eisenforschung GmbH (Germany). The image shows, symbolically, the investigation of the dissolution of carbon‐supported platinum nanoparticles by using a scanning flow‐cell‐based setup with on‐line detection of dissolution products through ICP–MS. Read the full text of the Article at 10.1002/celc.201500098.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…13,21,22 The classical testing protocols used to study cathode catalyst durability are fast potential variations from an Upper Potential Limit (UPL) ranging from 0.9 V to 1.2 V to a Lower Potential Limit (LPL) of 0.6 V to simulate cathode potential variations during transient operation (idle-to-peak) or up to an UPL of 1.2-1.5 V for startup/shutdown cycles simulation. [12][13][14]16,[23][24][25][26] All potentials herein are verses a Reversible Hydrogen Electrode (RHE) reference. The ECSA is typically periodically assessed during the ADT to correlate to performance losses.…”
Section: F1176mentioning
confidence: 99%
See 1 more Smart Citation
“…13,21,22 The classical testing protocols used to study cathode catalyst durability are fast potential variations from an Upper Potential Limit (UPL) ranging from 0.9 V to 1.2 V to a Lower Potential Limit (LPL) of 0.6 V to simulate cathode potential variations during transient operation (idle-to-peak) or up to an UPL of 1.2-1.5 V for startup/shutdown cycles simulation. [12][13][14]16,[23][24][25][26] All potentials herein are verses a Reversible Hydrogen Electrode (RHE) reference. The ECSA is typically periodically assessed during the ADT to correlate to performance losses.…”
Section: F1176mentioning
confidence: 99%
“…13,23 However, studies on Pt dissolution (from extended surfaces to supported nanoparticles) indicated that triangular waves lead to a higher dissolution of Pt at UPLs at or above 0.95 V. 23,27,28 More precisely, the dissolution seems to occur during the oxide layer reduction (cathodic sweep) and the amount of dissolved Pt is inversely proportional to the scan rate (1-100 mV sec −1 ) applied. 11,25,26,29 The ECSA loss due to increased number of ADT cycles shows initially a fast decay during the first 1000 perturbation cycles, followed by a gradual loss over an extended number of cycles. 14,30 To more fully track the decay process it is logical to increase the assessment frequency during the first several thousand ADT perturbations, although as shown herein the effects from this more frequent analysis would not correlate to actual automotive PEMFC life.…”
Section: F1176mentioning
confidence: 99%
“…Although they exhibit good activity, 9 state of the art precious-metal catalysts often suffer from insufficient stability due to the formation of an oxide layer 10 and metal dissolution during the ORR. 11,12 Non-precious-metal catalysts, including heteroatom-doped carbons 13 and transition metal (TM)/transition metal oxide (TMO)−carbon hybrids, 14 have been applied in ORR systems. TMO is generally used together with carbonaceous materials which function as the conducting agents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[9,11,13,21,22] As well as being determined by the intrinsic structural properties of the catalyst, the intensity of the dissolution of supported metal NPs tends to vary, depending on the applied operating conditions in energy conversion and storage devices. [23][24][25] For instance, hydrogen-bromine redox flow batteries (H 2 -Br 2 RFBs) involve highly reversible reactions at the anode and cathode side by flowing with H 2 gas and acid electrolyte composed of protons (H + ) and oxidizing Br x species. Platinum-based catalysts still serve as the most active H 2 -related electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, metal NPs dissolution usually occurs through direct chemical reactions with reactants and/or electrolyte components accompanied by (electro)catalytic oxidation and reduction processes [9,11,13,21,22] . As well as being determined by the intrinsic structural properties of the catalyst, the intensity of the dissolution of supported metal NPs tends to vary, depending on the applied operating conditions in energy conversion and storage devices [23–25] . For instance, hydrogen‐bromine redox flow batteries (H 2 ‐Br 2 RFBs) involve highly reversible reactions at the anode and cathode side by flowing with H 2 gas and acid electrolyte composed of protons (H + ) and oxidizing Br x species.…”
Section: Introductionmentioning
confidence: 99%